Effects of a trauma center on early mortality after trauma in a regional city in Japan: a population-based study. Issue 1 (2nd June 2019) - Takahashi, Yuji; Sato, Shuntaro; Yamashita, Kazunori; Matsumoto, Naoya; Nozaki, Yoshihiro; Hirao, Tomohito; Tajima, Goro; Inokuma, Takamitsu; Yamano, Shuhei; Takahashi, Kensuke; Miyamoto, Takashi; Inoue, Kenichiro; et al.
Abstract : Background: Although the effects of the trauma center(TC) were researched in several studies, there have been few studies on changes in the regional mortality due to the implementation of a TC. An emergency medical center (EMC) and TC were implemented at Nagasaki University Hospital (NUH) for the first time in the Nagasaki medical region of Japan in April 2010 and October 2011, respectively, and they have cooperated with each other in treating trauma patients. The purpose of this study was to investigate the effects on the early mortality at population level of a TC working in cooperation with an EMC. Methods: This is a retrospective study using standardized regional data (ambulance service record) in Nagasaki medical region from April 2007 through March 2017. We included 19, 045 trauma patients directly transported from the scene. The outcome measures were prognosis for one week. To examine the association between the implementation of the EMC and TC and mortality at a region, we fit adjusted logistic regression models. Results: The number of patients of each fiscal year increased from 1492 in 2007 to 2101 in 2016. The number of all patients transported to NUH decreased until 2009 to 70, but increased after implementation of the EMC and TC. Overall mortality of all patients in the region improved from 2.3% in 2007 to 1.0% in 2016.In multivariate logistic regression model, odds ratio of death was significantly smaller at 2013 and thereafter if the data from 2007 to 2011 was taken as reference. Conclusions: Implementation of the EMC and TC was associated with early mortality in trauma patients directly transported from the scene by ambulance. Our analysis suggested that the implementation of EMC and TC contributed to the improvement of the early mortality at a regional city with 500000 populations. Level of evidence: Level III.